Assessment of Rural Community Knowledge and Attitudes Toward Rational Antibiotic Use in Kampung Baru Hamlet, Seko District: Penilaian Tingkat Pengetahuan dan Sikap Masyarakat Pedesaan terhadap Penggunaan Antibiotik yang Rasional di Dusun Kampung Baru, Kecamatan Seko - Purnamasari P, Indah; Gisman, Rahmiaty; Aswandi, Aswandi; Arianto, Adi; Yuli Nurvianthi, Riska; Hervinto, Deris (Medical : Jurnal Kesehatan dan Kedokteran, 2026)
Rational antibiotic use is essential to prevent and treat infections effectively and to avoid harmful consequences such as antimicrobial resistance, increased adverse drug reactions, and higher treatment costs. This study aims to assess the level of knowledge and attitudes toward rational antibiotic use among residents of Kampung Baru Hamlet, Seko District. A descriptive observational study with a cross-sectional approach was conducted involving 100 respondents who met the inclusion criteria. The study found that knowledge regarding antibiotic use was categorized as good in 7% of respondents, moderate in 20%, and poor in 73%. Attitudes toward proper antibiotic use were categorized as good in 7%, moderate in 10%, and poor in 83% of respondents. Statistical analysis showed a significant relationship between the level of knowledge and attitudes toward antibiotic use (p = 0.001). These findings indicate that most of the community lacks adequate knowledge and appropriate attitudes regarding rational antibiotic use, highlighting the need for targeted health education programs to promote safer and more effective antibiotic practices